Home-Care Workers’ Representations of Their Role and Competences: A Diaphanous Profession - Gazzaroli, Diletta; D’Angelo, Chiara; Corvino, Chiara (Frontiers in Psychology, 2020)
Because of the gradual aging of the population hospital facilities for socio-sanitary care of the elderly are quite scarce relative to the very high number of elderly people present in the country. This has pushed a high number of families to privately hire home-care workers. The scientific literature gives a picture of the psycho-physical risks that this type of profession is exposed to; however, there is still a need for a more systemic reflection with regard to representations about role and competences. The aim of the present study is to outline the representations of the role and the skills it requires from home-care workers point of view. We reconstructed how home-care workers perceive and define the profession, and understand the necessary skills required from their point of view. Our results show that the professional profile of the home-care workers still remains poorly defined and that professionals themselves struggle to find value, recognition and to articulate what the skillset they develop is formed of.